2008
DOI: 10.1002/chir.20624
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective separation and degradation of the herbicide dichlorprop methyl in sediment

Abstract: Chiral pesticides currently constitute about 50% of all pesticides dosage used in China, and this ratio is increasing as more complex structures are introduced. Dichlorprop methyl (DCPPM) is a chiral herbicide consisting of a pair of enantiomers. In this study, the enantiomeric separation of DCPPM was investigated by gas chromatography (GC) and high-performance liquid chromatography (HPLC) using chiral stationary phases (CSPs), and its enantiomeric degradation was characterized using a DCPPM-degrading bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The indigenous microorganisms in the soil play an important role in the degradation of pesticides. The degradation difference of isomers might be due to selective degradation by soil microorganisms occurring at specific environments (Ma et al 2005). The same trend of degradation of a pesticide (imazapyr) was reported by Wang et al (2005).…”
Section: Gc Conditionsupporting
confidence: 67%
“…The indigenous microorganisms in the soil play an important role in the degradation of pesticides. The degradation difference of isomers might be due to selective degradation by soil microorganisms occurring at specific environments (Ma et al 2005). The same trend of degradation of a pesticide (imazapyr) was reported by Wang et al (2005).…”
Section: Gc Conditionsupporting
confidence: 67%
“…Dissipation studies and field-only experiments with no incubation experiments considered were left out [72,149,[156][157][158][159][160][161][162][163][164][165][166][167]. beta-cypermethrin soil laboratory incubation experiments under sterile and non-sterile conditions HPLC-VWD enantioselective degradation of beta-cypermethrin observed; different degradation rates observed for the four beta-cypermethrin isomers; EF variation noticed during the degradation process [143] beta-cypermethrinsoil laboratory incubation experiments under sterile and non-sterile conditions with acidic and alkaline matrices, and with racemic mixture and individual enantiomers HPLC-UV enantioselective degradation of racemic-beta-cypermethrin observed only in non-sterile soils; different degradation rates and half-lives observed for the four beta-cypermethrin isomers; no enantiomeric enrichment observed during degradation of individual enantiomers [144] Regarding the analytical methods used to quantify pesticides' enantiomers during biodegradation, the trend is clear and high-performance liquid chromatography with a diode array detector (HPLC-DAD) [117,122,123,126,128,134,135,140,152] and an ultraviolet detector (UV) [120,129,132,136,138,141,144,146,150,151,155], as well as liquid chromatography tandem-mass spectrometry (LC-MS/MS) [21,...…”
Section: Biodegradation Studies Of Chiral Pesticidesmentioning
confidence: 99%
“…Generally, all the studies reported enantioselective biodegradation to some extent in the various matrices considered (for instance, algae cultures, agricultural soil, sediment, water, and vegetables) [127][128][129][130]. Diclofop-methyl exhibited diverse enantioselective behaviors in different biodegradation matrices, with its (-)-enantiomer being degraded faster in soil samples and more slowly in Chinese cabbage samples [128].…”
Section: Biodegradation Studies Of Chiral Pesticidesmentioning
confidence: 99%
“…As in the case of other chiral pesticides (6,35), preferential degradation of either the R or the S enantiomer of dichlorprop during microbial degradation has been reported (13,22,26). (R,S)-Dichlorprop enantioselectivity is largely dependent upon the behavior of the microbial community at hand and can be influenced by factors such as pH (3,23), soil type (36), and the environment (e.g., soil, water, or sludge) (4,13,47). The enantioselectivity observed during the microbial transformation of chiral dichlorprop implies that enzymes involved in degradation of this compound are somehow able to differentiate between enantiomers.…”
mentioning
confidence: 97%